2011
DOI: 10.1159/000332048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Somatic Modulation between Somatic Tinnitus and Otic Tinnitus

Abstract: Aims:To compare the clinical characteristics of tinnitus among patients with somatic tinnitus (ST), otic tinnitus with somatic modulation (OT+) and otic tinnitus without somatic modulation (OT-), and to examine differences in somatic modulation between patients with ST and OT+. Methods: We retrospectively reviewed the medical records of 65 patients with unilateral tinnitus and classified the patients into three groups: ST (n = 24), OT+ (n = 21) and OT-(n = 20). Results: Only one difference in clinical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Of the head and neck maneuvers, jaw manipulations such as protruding, sliding or clenching usually produce the most modulation, which is consistent with the fact that tinnitus is common in patients with TMD [Abel and Levine, 2004;Simmons et al, 2008;An et al, 2011]. However, in general, jaw maneuvers have been reported to increase the loudness of tinnitus, whereas neck maneuvers tend to decrease loudness, which is consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of the head and neck maneuvers, jaw manipulations such as protruding, sliding or clenching usually produce the most modulation, which is consistent with the fact that tinnitus is common in patients with TMD [Abel and Levine, 2004;Simmons et al, 2008;An et al, 2011]. However, in general, jaw maneuvers have been reported to increase the loudness of tinnitus, whereas neck maneuvers tend to decrease loudness, which is consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 91%
“…No modulation with all 19 maneuvers occurred; tinnitus was modulated in 1 ear with 18 maneuvers. Table 4 shows the prevalence and direction of somatic modulation found in the present and six previous studies [Levine, 1999b;Sanchez et al, 2002;Levine et al, 2003;Abel and Levine, 2004;Sanchez et al, 2007;An et al, 2011]. The total prevalence of somatic modulation varied among studies (58-83%).…”
Section: Prevalence and Amount Of Somatic Modulationmentioning
confidence: 52%
“…To date, the correlation between higher percentages of tinnitus modulation and the presence of somatic disorders is still debated [Wright and Bifano, 1997;Sanchez et al, 2002;An et al, 2011;Vielsmeier et al, 2011Vielsmeier et al, , 2012. Such a connection, if present, could help identify tinnitus patients with underlying head/neck dysfunctions that could play a role in their tinnitus and patients who could benefit from further multidisciplinary investigation and physical therapy; the presence of tinnitus modulation in the somatic region for which the patient reported a positive history could be good evidence in support of this assumption.…”
Section: Introductionmentioning
confidence: 99%
“…Somatic modulation has been reported in approximately two-thirds of tinnitus patients 35,43 ; other studies revealed tinnitus modulation in 85% 45 TMJ is the most common affected region in patients with somatic tinnitus. Rubinstein studied 102 individuals with tinnitus reporting that about one-third of the patients had influence on tinnitus by mandibular movements and/ or pressure applied to the temporomandibular joint [63][64][65] and found that subjects with tinnitus had a significantly higher prevalence of cranio-mandibular disorders. Chole 58 found tinnitus to be significantly more prevalent among a group of 338 patients with TMJ disorders compared to 694 controls.…”
Section: Considerations On Somatic Modulation Of Tinnitusmentioning
confidence: 99%